Construction of a Digital and Physical Hybrid Simulation Platform for MMC-HVDC Grid With Fault Current Suppression Equipment - Wang, Weiru; Wang, Limeng; Zhu, Bo; Li, Guoqing; Xin, Yechun; Jiang, Shouqi (Frontiers in Energy Research, 2021)
In order to fully study the working characteristics of large-scale power electronic devices in the field of renewable energy delivery, it is imperative to build digital & physical hybrid simulation platforms. A power interface algorithm based on damping impedance is proposed by this paper for DC power grid digital & physical hybrid simulation to improve the stability of the platform. Firstly, according to the characteristics of open-loop transfer function of damping impedance method, the matching principle between damping impedance and equivalent impedance of physical simulation system is obtained. Secondly, the impedance of converter, DC circuit breaker and fault current limiter is analysed in detail, and the equivalent impedance of physical simulation system under different working conditions is discussed and calculated to realize the real-time matching of damping impedance. To compensate the power interface delay, a delay compensation method based on the slope prediction method is proposed for the DC voltage interface, and a prediction compensation model is constructed to reduce the simulation error caused by the delay. A digital & physical hybrid platform for a four-terminal flexible DC power grid with DC circuit breakers is built to verify the proposed interface algorithm. The simulation results show that the interface algorithm proposed in this paper can compensate the interface delay efficiently, and can ensure the stable operation of the platform under different working condition.